Right-Wing Psychedelia: Case Studies in Cultural Plasticity and Political Pluripotency - Pace, Brian A.; Devenot, Neşe (Frontiers in Psychology, 2021)
Recent media advocacy for the nascent psychedelic medicine industry has emphasized the potential for psychedelics to improve society, pointing to research studies that have linked psychedelics to increased environmental concern and liberal politics. However, research supporting the hypothesis that psychedelics induce a shift in political beliefs must address the many historical and contemporary cases of psychedelic users who remained authoritarian in their views after taking psychedelics or became radicalized after extensive experience with them. We propose that the common anecdotal accounts of psychedelics precipitating radical shifts in political or religious beliefs result from the contextual factors of set and setting, and have no particular directional basis on the axes of conservatism-liberalism or authoritarianism-egalitarianism. Instead, we argue that any experience which challenges a person's fundamental worldview—including a psychedelic experience—can precipitate shifts in any direction of political belief. We suggest that the historical record supports the concept of psychedelics as “politically pluripotent,” non-specific amplifiers of the political set and setting. Contrary to recent assertions, we show that conservative, hierarchy-based ideologies are able to assimilate psychedelic experiences of interconnection, as expressed by thought leaders like Jordan Peterson, corporadelic actors, and members of several neo-Nazi organizations.